A hist??ria das m??dias e tecnologias na educa????o e no ensino de f??sica: a vis??o de alguns de sues protagonistas - Pucci, Luis F??bio Sim??es (2007)
The contemporary society is strongly based on the use and development of technologies, which, under one of their aspects, are presented as fast and powerful means of information and communication. As it could not fail to be, such reality has influences also on the field of Education: books, newspapers, television, video, computers, several pieces of teaching equipment and educational systems, among others, are seen as potential educational media, both inside and outside school. However, according to a survey made with high school students of the public chain of the State of S??o Paulo itself, classroom practices performed by teachers of the public chain still seem to be poorly backed by the several media and technology resources available. In particular, great programs inside the field of Physics, which included the use of teaching support and professional development materials, might have helped discover new paths for education, but they certainly have not been able to transform teaching practices significantly. The purpose hereof is, from the history standpoint, try to see why this occurs, by relying on the opinion of experts who played an important role to implement programs in this field, as well as by attempting to go beyond the most obvious reasons, such as shortcomings in the education given to high school teachers.